PERENCANAAN STRUKTUR GEDUNG HOTEL FAVE SOLO BARU - Bangkit Andri Yulianto; Dwi Agus Nugroho; Himawan Indarto; Ilham Nurhuda (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
In case of building structure plan, analyzing of earthquake effect is important. Especially for building which located in big earthquake zones. Indonesian isles are situated on major earthquake zones. That’s why the good planning are needed to manage earthquake risk to avoid big accident. On this final paper, the building are planned with Sway Special Design System. That based on SNI 03-2847-2002 and SNI 1726-2010. “Strong Column Weak Beam” concept is used for the building. The planning of structure are consist of 14 levels and 2 basements which located in 3rd earthquake zone. We expected that Sway Special Design System can be good applicated and useful for all of people on building plan which located in major earthquake zone.